Effleurage Massage using Rose Essential Oil in Reducing the Intensity of Dysmenorrhea Pain in Adolescent Girls - Mayasari Putri Ardela; Nara Lintan Mega Puspita (Institut Ilmu Kesehatan STRADA Indonesia, 2023)
Background: Dysmenorrhea is pain in the lower abdomen during menstruation which is generally caused by contractions of the myometrium due to prostaglandin production. In Indonesia, 43-93% girls experiencing dysmenorrhea. Effleurage massage using rose essential oil is one of the non-pharmacological methods that can be used to reduce the intensity of pain during dysmenorrhea. Purpose: The purpose of this study was to determine the effect of effleurage massage using rose essential oil on the intensity of dysmenorrhea pain in adolescent girls. Methods: This study used a quasi-experimental design with a type of non-equivalent control group design. The sample in this study amounted to 24 people who would be divided into 4 treatment groups, namely treatment groups 1 and 2 given effleurage massage using rose essential oil and control groups 1 and 2 given effleurage massage using almond oil, with the duration of each group's massage for 15 minutes and 10 minutes. Data analysis was performed using the Two Way Anova test. Results: The most effective action in reducing the intensity of dysmenorha pain is effleurage massage using rose essential oil for 15 minutes based on the mean value of the Two Way Anova test which is 3.83, and the significance number for massage duration variable 0.015 (significant). Conclusion: The effleurage massage method using rose essential oil can be used as one of the non-pharmacological therapeutic methods in reducing the intensity of dysmenorrhea pain that is easy to apply, especially for adolescent girls when experiencing menstrual pain.